1999
DOI: 10.1159/000026386
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of One and Repeated Endotoxin Treatment on Pituitary- Adrenocortical Hormones in the Mouse: Role of Interleukin-1 and Tumor Necrosis Factor-α

Abstract: The role of endogenous interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in modulating the hypothalamic-pituitary-adrenal (HPA) axis response was examined in male C57BL/6 mice injected with endotoxin (lipopolysaccharide, LPS) or saline at 24-hour intervals for 4 or 8 consecutive days. The mice were divided into four groups: (1)  LPS injections for 4 or 8 days and LPS injection on day 5 or 9, respectively (LPS-LPS); (2) LPS injections for 4 or 8 days and saline injection on day 5 or 9, respectively (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…In the current report, LPS exposure induced plasma IL-1β release and increased IL-1β and IL-6 gene expression in hippocampus in salinetreated and diclofenac-treated rats. The cytokine activation responses in the current report are similar to those previously reported following acute LPS and IL-1β exposure (Laye et al 1994;Lenczowski et al 1997;Nagano et al 1999;Turrin et al 2001). The current data may coincide with a recent report showing that an NSAID attenuated anorexia during systemic inflammation without impairing cytokine production (Johnson et al 2002).…”
Section: Discussionsupporting
confidence: 88%
“…In the current report, LPS exposure induced plasma IL-1β release and increased IL-1β and IL-6 gene expression in hippocampus in salinetreated and diclofenac-treated rats. The cytokine activation responses in the current report are similar to those previously reported following acute LPS and IL-1β exposure (Laye et al 1994;Lenczowski et al 1997;Nagano et al 1999;Turrin et al 2001). The current data may coincide with a recent report showing that an NSAID attenuated anorexia during systemic inflammation without impairing cytokine production (Johnson et al 2002).…”
Section: Discussionsupporting
confidence: 88%
“…The present results clearly demonstrate that the decrease of IL-1 receptors in vivo is not due to a direct effect of LPS since IL-1 receptors are increased in AtT-20 cells in vitro while available receptors in vivo are decreased followed by LPS treatment. Our previous studies demonstrated that IL-1ß concentrations were increased in plasma and in the hippocampus, pituitary, adrenal gland 2 h after LPS injection [14,25], suggesting that high ligand concentrations remained in the tissues. Furthermore, 1 nM IL-1ß significantly decreased IL-1 receptors in AtT-20 cells compared with the control group in the present study, supporting that the rather high ligand concentration causes receptor occupancy and downregulation.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, LPS significantly stimulated adrenal IL-1ß production in 24-week-old mice compared with the saline group. Of the three tissues (hippocampus, hypothalamus and adrenal gland) examined, basal concentrations of IL-1ß were, by far, highest in the adrenal gland, followed by the hypothalamus and hippocampus [40]. In the present study, saline-induced (basal) IL-1ß concentrations in the adrenal gland were approximately 25-40 times higher than those in the hippocampus and hypothalamus, which may be responsible for the differences in the agerelated modulation of IL-1ß levels by LPS in 7-and 24-week-old mice.…”
Section: Discussionmentioning
confidence: 97%